Developing a standardized approach to prenatal counseling following the diagnosis of a complex congenital heart abnormality. (December 2021) - Gendler, Yulia; Birk, Einat
Highlights: Pediatric cardiologist provides couples with information, guidance and support. Standardized counseling leads to high parental satisfaction with the counseling process. Standardized counseling is associated with high cardiologists ability to predict parental decision.